Redox Metabolism in Ecophysiology and Evolution - Daniel C. Moreira; Tania Zenteno-Savín; Marcelo Hermes-Lima (MDPI AG, 2023)
Aerobic organisms have developed a complex system of endogenous antioxidants to manage the reactivity of oxygen and its byproducts [...]